2019
DOI: 10.1111/deci.12381
|View full text |Cite
|
Sign up to set email alerts
|

Postdisaster Volatility of Blood Donations in an Unsteady Blood Supply Chain*

Abstract: The stochastic behavior of both transfusion (demand) and blood donations (collection) is a challenge for the blood supply chain. Although donations are not fully within the control of blood supply chain, the blood service can marginally moderate it by postponing appointments in the case of having an overstock, or by triggering a call for additional blood when faced with shortages. Such shortages are often observed as a consequence of catastrophic events. Past studies show that the response to a call for blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…Inventory management for the flow of blood and/or blood products in the supply chain is another important subject study in the literature. Ensafian et al ( 2017 ), Ensafian and Yaghoubi ( 2017 ), Osorio et al ( 2017 ), Hosseinifard and Abbasi ( 2018 ), Clay et al ( 2018 ), Hosseinifard et al ( 2020 ) can be shown as recent examples. In addition, Ghandforoush and Sen ( 2010 ), Şahinyazan et al ( 2015 ), Blake et al ( 2015 ), Gunpinar and Centeno ( 2016 ), Elalouf et al ( 2018 ) focus on the logistics of blood products in the supply chain.…”
Section: Literature Surveymentioning
confidence: 96%
“…Inventory management for the flow of blood and/or blood products in the supply chain is another important subject study in the literature. Ensafian et al ( 2017 ), Ensafian and Yaghoubi ( 2017 ), Osorio et al ( 2017 ), Hosseinifard and Abbasi ( 2018 ), Clay et al ( 2018 ), Hosseinifard et al ( 2020 ) can be shown as recent examples. In addition, Ghandforoush and Sen ( 2010 ), Şahinyazan et al ( 2015 ), Blake et al ( 2015 ), Gunpinar and Centeno ( 2016 ), Elalouf et al ( 2018 ) focus on the logistics of blood products in the supply chain.…”
Section: Literature Surveymentioning
confidence: 96%
“…Recently, quantitative models have been used to study aspects of the blood supply chain in disaster relief situations which make use of multi-objective programming (Samani et al, 2018), robust optimisation (Jabbarzadeh et al, 2014) and Markov chains (Hosseinifard et al, 2019). Other supply chain approaches include mathematical optimisation models for finding appropriate delivery routes for blood supplies (Ezugwu et al, 2019;Kazemi et al, 2017).…”
Section: Quantitative Modelsmentioning
confidence: 99%
“…In addition, the model in (Perry and Posner, 1990) can only deal with one or two switch-over levels, which limits the generalisation to more complex scenarios with a large number of input or output rates to choose from, each with its own characteristics in terms of costs incurred. In contrast, blood inventory optimisation models typically consider two dichotomous situations: normal and emergency (e.g., Kopach et al, 2008;Hosseinifard et al, 2019). Closed-form solutions are usually obtained with a view to maintaining the blood supply at an operationally satisfactory level.…”
Section: Quantitative Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Keeping the balance between shortage and outdate of blood is the major challenge related to the management of the blood inventory at hospitals [41]. Due to the perishable nature of blood, having an excessive number of blood units in inventory would inevitably increase wastage [20].…”
Section: Introductionmentioning
confidence: 99%